An assay to determine the sensitive window of embryos to chemical exposure using Xenopus tropicalis. Issue 5 (14th July 2015) - Hu, Lingling; Wu, Lijiao; Xue, Yingang; Zhu, Jingmin; Shi, Huahong
Abstract: The frog embryo teratogenesis assay‐ Xenopus (FETAX) is an established method to evaluate the developmental toxicity of chemicals. In FETAX, a 48 h continuous exposure is usually conducted when the X . tropicalis embryo is used as the test model. In the present study, we exposed X . tropicalis embryos to nine known teratogens for four separate 12‐h periods. The embryos showed great variations in response to nine tested compounds during different exposure periods. Based on the value of the score of malformations, the most sensitive 12 h exposure periods of embryos were significantly distinguished for all the compounds with the exception of NiCl2 . The embryos were the most sensitive to retinols (e.g. all‐trans ‐retinoic acid and 9‐cis ‐retinoic acid) during 0–12 h and to metal compounds (e.g. triphenlytin and CdCl2 ) during a 24 to 36 h exposure period. In the further 3 h exposure experiment, the most sensitive period could only be determined for one of three tested compounds. Based on the present results, we proposed an assay to determine a 12 h sensitive window of embryos to chemical exposure using Xenopus tropicalis . Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The Xenopus tropicalis embryos showed great variations of malformation in response to nine tested compounds during four separate 12‐h exposure periods. Based on the value of score of malformations, the most sensitive exposure period of embryos was significantly distinguished for eight compounds. A rapid and valid assay was proposed to determine the 12‐h sensitive window of embryos to chemical exposure using X . tropicalis .